The Devil in Mr. Smith: A Conversation with Jonathan Z. Smith. (January 2014) - Smith, Jonathan Z.; Pearson, Thomas; Gallagher, Eugene V.; Jensen, Tim; Fujiwara, Satoko
Abstract This interview was recorded in November 2012 in Jonathan Z. Smith's Hyde Park graystone. Professor Smith offers insights into how he thinks about his classroom teaching and his students' learning through descriptions of various assignments and classroom activities he has developed over more than forty years of teaching. The discussion ranges broadly over such topics as: how students read, the failure to adequately prepare graduate students as teachers, students' faith commitments, the use of newspapers (and humor) in the classroom, and the role of definition, de‐familiarization, and critique of the study of religion in introductory classes. The discussion presents vivid glimpses into Jonathan Smith's teaching practice and his teaching persona, including the time a student brought a minister to class to do an exorcism because she thought he was the Devil.